Disfungsi Dispensasi Kawin dalam Upaya Pencegahan Perkawinan Anak - Suryanti, Irma; Rudy, Dewa Gde (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021), 2021)
This legal research purposes to examine the dysfunction of marriage dispensation to prevent child marriage. This scientific article uses a socio-legal research method which combine doctrinal legal research methods and empirical legal research methods through statutory approach, conceptual approach, and facts approach. This study results indicate that Law 16/2019 has not been able to prevent child marriage. The court was expected as last effort in preventing child marriage, but in the end failed to carry out its function. The lack of judge’s courage in legal finding efforts causes judges to prioritize legal benefits, however judges neglect to consider the child marriage negative impact, so that the majority of marriage dispensation applications were granted. The urgency of standardizing the marriage dispensation regulation and ratification needed of the Draft Law on the Religious Courts which regulates criminal sanctions and fines for perpetrators of child marriage and the party carrying out child marriage. The demand for the government role as a policy maker to prevent child marriage needs to be maximized, so that society can obey the law in order to avoid the impact of child marriage which will harm children a lot. Apart from the roles of various parties, the role of parents is the main role in preventing child marriage in the child protection update as mandated by Law 23/2002 in conjunction with Law 35/2014. Tujuan penelitian ini untuk mengkaji disfungsi dispensasi kawin dalam upaya pencegahan perkawinan anak. Artikel ilmiah ini menggunakan metode penelitian sosio-legal yang menggabungkan metode penelitian hukum doktrinal dan metode penelitian hukum empiris melalui pendekatan undang-undang, pendekatan konseptual, dan pendekatan fakta. Hasil penelitian ini menunjukkan UU 16/2019 belum dapat mencegah perkawinan anak. Pengadilan yang diharapkan sebagai upaya terakhir dalam pencegahan perkawinan anak, namun pada akhirnya gagal menjalankan fungsinya. Minimnya keberanian hakim dalam upaya penemuan hukum menyebabkan penetapan hakim lebih mengutamakan kemanfaatan hukum, namun hakim lalai untuk mempertimbangkan dampak negatif dari perkawinan anak sehingga mayoritas permohonan dispensasi kawin dikabulkan. Urgensi standarisasi regulasi dispensasi kawin dan perlunya pengesahan RUU Hukum Terapan Peradilan Agama yang mengatur sanksi pidana dan sanksi denda bagi pelaku perkawinan anak dan pihak yang melangsungkan perkawinan anak tersebut. Tuntutan peran pemerintah sebagai pembuat kebijakan upaya pencegahan perkawinan anak perlu dimaksimalkaan, sehingga masyarakat dapat patuh dan taat pada hukum guna menghindari dampak perkawinan anak yang akan banyak merugikan anak. Terlepas dari peran berbagai pihak, maka peran orang tua adalah peran yang utama untuk mencegah terjadinya perkawinan anak dalam upaya perlindungan anak sebagaimana diamanatkan oleh UU 23/2002 jo UU 35/2014 tentang Perlindungan Anak.